Discourses in conflict: resource inequality, class warfare and home repossessions. Issue 3 (27th May 2017) - Block, David
ABSTRACT: The topic of this paper is an ongoing discursive conflict which has arisen in Spain around home repossession and home evictions, understood here as part of a more general class warfare waged by the financial elites on the popular classes. Firmly grounded in political economy and Critical Discourse Analysis (CDA), it examines attempts by the governing Partido Popular to represent as undemocratic a particular kind of protest action called escraches, which have been carried out by the Platform for People Affected by Mortgages, an organization which defends the rights of evictees. The key argument in this paper is that resource inequality, endemic to capitalism, has been aggravated and intensified during the current economic crisis, and that there is the need for more CDA research which is grounded in political economy to explore how events on the ground are mediated by discourses in conflict.